Building Student Commitment to Agricultural Safety: A Guide for Agriculture Education Classes - Rob Brown; Carol J. Lehtola; Charles M. Brown (EDIS, 2004)
This publication outlines a safety packet that youth in Pasco County agriculture courses are required to complete before taking classes. This packet must be read and signed by both the student and their parents so that everyone is aware of what they will be working with and equally aware of the safety attitude that is needed. This packet can be helpful for other schools to use as a guide for developing a safety commitment packet. This model was approved by the Pasco County School Board as well as their legal counsel. This document is ABE353, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Sciences, University of Florida. First published July 2004.